A Comparative Study on E?ects of Bupivacaine- Lignocaine and Bupivacaine- Lignocaine with Dexmedetomidine Combination in Ultrasound Guided Supraclavicular Brachial Plexus Block - P. Rajeswar; MN Girish (Academia Anesthesiologica International, 2020)
Background: To compare the effects of Bupivacaine Lignocaine and Bupivacaine Lignocaine in the ultrasound-guided Supraclavicular brachial plexus block with a mixture of Dexmedetomidine. Subjects and Methods: It is an interventional study undertaken over a course of 9 months in 60 patients undergoing elective upper limb surgery in the anaesthesia clinic of the Tertiary Centre. Sixty patients were allocated randomly to 2 groups, group I and group II. Effects on the onset and length of sensory and motor blockade and on the extent of postoperative analgesia may be studied. Results: Demographic data are equivalent in all grades. There is no significant change in hemodynamic parameters in comparison to the 2 groups. The onset of the sensory blockade and motor blockade in Group B was much smaller. With additional time in Group-B, the length of the sensory blockade and the motor blockade is statistically significant. Compared to A, the duration of complete sensory recovery and full motor recovery time forecast was longer in category B. In group-B at 0 and 4, the duration of complete analgesia at VAS is considerably long. Among the research classes, the length of maximal analgesia and the time of first rescue pain relief are statistically important. In the study, no complications were found. Conclusion: As an adjuvant to bupivacaine in the USG supraclavicular plexus block, dexmedetomidine shortens the onset and prolongs the sensory and motor block length.